G Protein-Coupled Estrogen Receptor Immunoreactivity Fluctuates During the Estrous Cycle and Show Sex Differences in the Amygdala and Dorsal Hippocampus - Llorente, Ricardo; Marraudino, Marilena; Carrillo, Beatriz; Bonaldo, Brigitta; Simon-Areces, Julia; Abellanas-Pérez, Pedro; Rivero-Aguilar, Marina; Fernandez-Garcia, Jose M.; Pinos, Helena; Garcia-Segura, Luis M.; Collado, Paloma; Grassi, Daniela (Frontiers in Endocrinology, 2020)
G protein-coupled estrogen receptor (GPER) in the amygdala and the dorsal hippocampus mediates actions of estradiol on anxiety, social recognition and spatial memory. In addition, GPER participates in the estrogenic regulation of synaptic function in the amygdala and in the process of adult neurogenesis in the dentate gyrus. While the distribution of the canonical estrogen receptors α and β in the amygdala and dorsal hippocampus are well characterized, little is known about the regional distribution of GPER in these brain regions and whether this distribution is affected by sex or the stages of the estrous cycle. In this study we performed a morphometric analysis of GPER immunoreactivity in the posterodorsal medial, anteroventral medial, basolateral, basomedial and central subdivisions of the amygdala and in all the histological layers of CA1 and the dentate gyrus of the dorsal hippocampal formation. The number of GPER immunoreactive cells was estimated in these different structures. GPER immunoreactivity was detected in all the assessed subdivisions of the amygdaloid nucleus and dorsal hippocampal formation. The number of GPER immunoreactive cells was higher in males than in estrus females in the central (P=0.001) and the posterodorsal medial amygdala (P<0.05); higher in males than in diestrus females in the strata orients (P<0.01) and radiatum-lacunosum-moleculare (P<0.05) of CA1-CA3 and in the molecular layer of the dentate gyrus (P<0.01); higher in diestrus females than in males in the basolateral amygdala (P<0.05); higher in diestrus females than in estrus females in the central (P<0.01), posterodorsal medial (P<0.01) and basolateral amygdala (P<0.01) and higher in estrus females than in diestrus females in the strata oriens (P<0.05) and radiatum-lacunosum-moleculare (P<0.05) of CA1-CA3 and in the molecular layer (P<0.05) and the hilus of the dentate gyrus (P<0.05). The findings suggest that estrogenic regulation of the amygdala and hippocampus through GPER may be different in males and in females and may fluctuate during the estrous cycle.